Museums and the construction of disciplines : art and archaeology in nineteenth-century Britain - Whitehead, Christopher, 1972- (Debates in archaeology., 2009)
Museums and museum politics were important elements in the development of the disciplines of Archaeology and Art History in nineteenth-century Britain. Here Christopher Whitehead explores some of the key debates and events which led to the conceptual differentiation and physical separation of 'archaeological' and 'artistic' material culture, looking especially at the ways in which objects and histories were contested within museum politics. For example, in the 1850s, the status of Egyptian antiquities as 'art' or 'archaeology' was keenly debated, and this related closely to questions about whi.